Współczesne zmiany kulturowo-komunikacyjne a język prawa. Uwagi na marginesie propozycji nowego modelu uzasadnienia orzeczeń sądowych - Nowak, Paweł; Rutkowski, Mariusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The subject of the article is the structure and linguistic shape of a specific type of legal genre – the reasons for the judgement. The authors, as members of the project and training team, actively participate in the transformation of the communication standards for the Polish judiciary community. They work with the assumption that the long-standing tradition of legal communication is hermetic and results in texts which are uncommunicative and unintelligible to an average reader. In the article, the authors present the social, media, linguistic and communication contexts of such texts. They emphasise their retropical character and indicate the possible direction of changes towards less hermetic and more everyday communication experiences, closer to the average reader. In the conclusion, they underline the importance of the intelligibility of a text as the basic parameter of effective communication and advocate for a systemic change of contemporary legal communication. Based on the texts of reasons for the judgement, they show that such a change is possible as long as it is accepted by the judiciary community in the first place.